2018
DOI: 10.1002/hpja.192
|View full text |Cite
|
Sign up to set email alerts
|

Reducing stress and burnout in the public‐sector work environment: A mindfulness meditation pilot study

Abstract: Qualitative results extend comparable quantitative research by detailing how an appropriately tailored 8-week meditation-based program has the potential to decrease perceived stress in highly stressful work environments. SO WHAT?: Triangulated data suggest that an appropriately adapted mindfulness meditation program can be an effective, efficient and low-cost inclusion within an organisation's health promotion repertoire to help increase mental health among staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
0
16
0
2
Order By: Relevance
“…In organizational settings, mindfulness-based programs have shown positive outcomes in terms of stress reduction [ 38 ], reduced emotional exhaustion and turnover intentions [ 39 ], reduced burnout [ 40 ], as well as well-being promotion (e.g., [ 41 ]). Mindfulness-based programs at work have also been shown to help increase concentration, cognitive abilities such as attentional control and cognitive flexibility, as well as emotion regulation and behavioral flexibility (reducing automatic behaviors triggered by stressful situations, for example), and have also been shown to increase performance at work and inter-personal relationships (e.g., [ 31 ]).…”
Section: Introductionmentioning
confidence: 99%
“…In organizational settings, mindfulness-based programs have shown positive outcomes in terms of stress reduction [ 38 ], reduced emotional exhaustion and turnover intentions [ 39 ], reduced burnout [ 40 ], as well as well-being promotion (e.g., [ 41 ]). Mindfulness-based programs at work have also been shown to help increase concentration, cognitive abilities such as attentional control and cognitive flexibility, as well as emotion regulation and behavioral flexibility (reducing automatic behaviors triggered by stressful situations, for example), and have also been shown to increase performance at work and inter-personal relationships (e.g., [ 31 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Os diferentes formatos de entrega do MBSR e o uso do protocolo padrão do programa CARE, em dois estudos, indicaram efeitos positivos da atenção plena na síndrome de burnout, consolidando as evidências de outras pesquisas com o primeiro protocolo (Frank et al, 2015;Todd, Cooksey, Davies, McRobbie, & Brophy, 2019) e o segundo Schussler, Jennings, Sharp, & Frank, 2016). Nos dois tipos de intervenção, o decréscimo da componente emocional foi um aspecto recorrente, corroborando achados de pesquisas com outros trabalhadores (Roy et al, 2020;Vella & McIver, 2019). A exaustão emocional é um dos primeiros estágios do esgotamento profissional (Benevides-Pereira, 2010), e representa o engajamento contínuo da pessoa em reações e respostas automáticas, sem atenção aos processos cognitivos e emocionais experimentados no momento presente (Kabat-Zinn, 2017).…”
Section: Discussionunclassified
“…Therefore, Hayat, Azeem, Nawaz, Humayon and Ahmed (2019) revealed that human capital, organisational culture, teamwork, organisational development and commitment have a substantial relationship. On a different concept, Vella and McIver (2019) showed that a meditation-based programme has the potential to decrease stress in a stressful work environment. Additionally, Tuan, Rowley and Thao (2019) provided that there is a moderating role of diversity-oriented leadership as well as group diversity.…”
Section: Introductionmentioning
confidence: 99%